FAKTOR PENYEBAB TERDORONGNYA WANITA PERNAH MENIKAH DAN SUDAH MENIKAH MELAKUKAN KEJAHATAN - Frinaldi, Aldri (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
This research aimed to reveal the factors that motived the married women and whoever has ever married to do the crime. This research used qualitative approach and descriptive method by describing the facts and investigating phenomenon systematically. The finding of this research indicated that behavior of married women and women who has ever married tended to change and differ from those they had when they were not yet married. The changes of this behavior was generally encouraged by economic motive. Key words: crime, married women, economic motive